Del estado pluricultural y multiétnico (1998) al estado plurinacional e intercultural (2008): “comunidades (no) imaginadas”, etnicidad y poder - Cahuasquí Cevallos, Santiago Manuel (2017)
The current essay is a debate-promoting document aimed to enrich such debate, gathering the most up-to-date references from those who have reflected upon in academic areas, as well as in political and social actions. The main question to be answered is linked to what have been the contextual characteristics of Ecuador’s cultural diversity management models in its construction process as an ‘imagined community.’ For that, the reference used is the way in which the 1998 and 2008 Constitutions have defined the State as ‘pluricultural and multiethnic’ and ‘intercultural and plurinational’, respectively. The objectives of this research are: (1) to analyze the accumulated resistance and insurgency of indigenous and Afro-descendant peoples, until their constitution as historical and political subjects; (2) to perform a conceptual approach to multiculturalism, multiculturalism and interculturality; and, (3) to establish the fundamental differences between the monocultural and uninational State; and the intercultural and plurinational State. The essay consists of three sections. The first comprises a brief look over the cumulus of resistances and insurgencies from the indigenous movement, starting in the Colony period until the 1990 uprising. The second section aims to explore the conceptual differences between pluriculturality and multiculturalism as State methods of managing cultural diversity. It also addresses the ‘imagined community’ category to substantiate why the nation is a cultural artifact—rather than an ideology—where the sense of Ecuadorian belonging is devised and enounced. The third section debates to what extent the State is acknowledged as plurinational. In the methodological aspect, the foundation was the bibliographical research, complemented qualitatively with the development of fieldwork through interviews with relevant actors of the indigenous world. In this way, this research sought to collect the own points of view of the social actors and such of their universes of meanings. The main conclusion is that the concepts of interculturality and plurinationality are part of a political dispute over the control of meanings and senses that fluctuate between usurpation and symbolic insurgency. However, exclusion, domination and violence have been the main characteristic of the models of management of diversity by the State, as well as of the conformation of the nation as an "imagined community".